Analisis Karakteristik Ruang Terbuka Hijau Publik di Kota Klaten Tahun 2025 - Ardhia Kusuma Ningrum (ENVIRO: Journal of Tropical Environmental Research, 2026)
This study aims to analyze the characteristics of Public Green Open Space in Klaten City in 2025. This study is a quantitative descriptive study with a spatial approach. Data collection techniques are carried out by image interpretation, field observation, interviews, and documentation. The results of this study are (1) The availability of Public Green Open Space in Klaten City in 2025 is 101.62 Ha or 2.83% of its area. (2) The characteristics of Public Green Open Space in Klaten City vary from good, moderate, to bad categories. Parks with good characteristic categories (score ≥ 24) are Taman Lantern, Alun-Alun Klaten, and Klaten City Park, parks with moderate characteristic categories are Taman Gergunung (score 23), and parks with bad characteristic categories are Taman Gayamprit & Hutan Kota Sungkur (score ≤19). The main form of direction for developing Public Green Open Space in Klaten City is to maintain the existing Public Green Open Space, increase the area of Public Green Open Space, and improve its characteristics through monitoring such as monitoring the quality of vegetation and Public Green Open Space facilities.